Cyber security and safety of nuclear power plant instrumentation and control systems - Yastrebenetsky, Michael A.; Charčenko, Vjačeslav (IGI Global, 2020)
"This book examines methods of cyber security and safety in nuclear power plant instrumentation and control systems"--